TEACHERS’ ASSESSMENT OF THE AVAILABILITY AND USE OF INSTRUCTIONAL MATERIALS FOR THE TEACHING OF VOCATIONAL SUBJECTS - Oyebola, Adetayo Janet (Sokoto Educational Review, 2008)
This study was conducted to assess the availability and utilization of instructional materials for the teaching of vocational subjects in secondary schools. The study adopted a survey design. A total of four hundred vocational subjects teachers drawn from two Local Government Areas of Ogun State were used for the study. The results of the study revealed that most of the listed instructional materials are not available in schools and where they are available they are not in good conditions. However, the study also revealed that there is a significant difference in the usage of the available instructional materials according to teachers’ qualifications. The paper, however, emphasized the need to ensure immediate supply of necessary teaching facilities into the schools if the aim of moulding the students self-reliant is to be achieved in the country.